Once a ranger [large type] - Richards, Dusty (Thorndike Press, A part of Gale, Cengage Learning, 2014)
Ex-Ranger Phil Guthrey swore he'd never stop roaming the West, bringing justice to the lawless. But after cleaning up Crook County, Arizona, he finds himself not only elected county sheriff but settling down with a pretty, young wife. Except keeping the peace in Crook County is less relaxing than Guthrie would have imagined. Border bandits accustomed to raiding the territory at will are not too keen on giving up the practice. Between his new wife and a town under threat, this former Texas Ranger is in for more than his fair share of action.